Two-Stage Management of the Infected Total Hip Arthroplasty. Issue 4 (July 2015) - Sandiford, Nemandra A.; Duncan, Clive P.; Garbuz, Donald S.; Masri, Bassam A.
There is currently no consensus on the optimal management of the infected total hip arthroplasty. Multiple management techniques have been described in contemporary literature. This paper focuses on 2-stage revision for the infected total hip arthroplasty. We discuss the rationale and examine the current evidence for the use of this technique.